STRATEGI PENGEMBANGAN USAHATANI JERUK DI DESA KEDAMPUL, MALANG, JAWA TIMUR - Hamidah Hendrarini; Hanggita Adwaa Saputri; Prasmita Dian Wijayati (AGRIBIOS, 2025)
This study aims to determine the internal and external factors of sweet orange farming in Kedampul Village, Tumpang District, East Java Regency, and to determine alternative development strategies. The method used in this study is qualitative, conducted purposively, where the questionnaire serves as the main tool for data collection. The data obtained were analyzed using SWOT. The results of the study indicate that alternative strategies implemented in orange farming in Kedampul Village are improving agricultural institutions, striving to improve farmers' human resources, good agricultural practice (GAP) cultivation management standards, and farmers and the government making marketing channels more effective for sustainable, progressive farming and wider marketing. In addition, the results of the SWOT analysis show that the internal factor score is greater than the external factor score of 2.428, the results of the SWOT analysis are located in the sweet orange farming development strategy quadrant. This study provides practical implications for farmers to optimize orange farming through improving business management, expanding wider marketing channels.